ASCCP Colposcopy Standards: Role of Colposcopy, Benefits, Potential Harms, and Terminology for Colposcopic Practice. Issue 4 (October 2017) - Khan, Michelle J.; Werner, Claudia L.; Darragh, Teresa M.; Guido, Richard S.; Mathews, Cara; Moscicki, Anna-Barbara; Mitchell, Martha M.; Schiffman, Mark; Wentzensen, Nicolas; Massad, L. Stewart; Mayeaux, E.J.; Waxman, Alan G.; et al.
Abstract : Objectives: The American Society for Colposcopy and Cervical Pathology Colposcopy Standards address the role of and approach to colposcopy and biopsy for cervical cancer prevention in the United States. Working Group 1 was tasked with defining the role of colposcopy, describing benefits and potential harms, and developing an official terminology. Methods: A systematic literature review was performed. A national survey of American Society for Colposcopy and Cervical Pathology members provided input on current terminology use. The 2011 International Federation for Cervical Pathology and Colposcopy terminology was used as a template and modified to fit colposcopic practice in the United States. For areas without data, expert consensus guided the recommendation. Draft recommendations were posted online for public comment and presented at an open session of the 2017 International Federation for Cervical Pathology and Colposcopy World Congress for further comment. All comments were considered for the final version. Results: Colposcopy is used in the evaluation of abnormal or inconclusive cervical cancer screening tests. Colposcopy aids the identification of cervical precancers that can be treated, and it allows for conservative management of abnormalities unlikely to progress. The potential harms of colposcopy include pain, psychological distress, and adverse effects of the procedure. A comprehensive colposcopy examination should include documentation of cervix visibility, squamocolumnar junction visibility, presence of acetowhitening, presence of a lesion(s), lesion(s) visibility, size and location of lesions, vascular changes, other features of lesion(s), and colposcopic impression. Minimum criteria for reporting include squamocolumnar junction visibility, presence of acetowhitening, presence of a lesion(s), and colposcopic impression. Conclusions: A recommended terminology for use in US colposcopic practice was developed, with comprehensive and minimal criteria for reporting. Abstract : The role, benefits, and potential harms of colposcopy are reviewed. A standardized terminology for colposcopic practice in the United States is presented.